Gunther Kress & Theo van Leeuwen, Reading Images. The Grammar of Visual Design - Bertoša, Mislava (Array, 2006)
Prikaz knjige koju su napisali Gunther Kress i Theo van Leeuwen, Reading Images. The Grammar of Visual Design.